Secret mall apartment [videorecording (DVD)] - Eisenberg, Jesse, 1983-; Townsend, Michael (Tape artist); Bliss, Colin; Valdez-Young, Adriana; Mercer, James, J. A.; Oesch, Andrew; Scheing, Greta; Ustach, Emily; Zehngebot, Jay (Music Box Films, 2025)
In 2003, eight Rhode Island artists created a secret apartment inside a mall and lived there for four years, filming everything along the way. Far more than just a wild prank, it became a deeply meaningful place for its inhabitants in this astonishing true story about discovering your purpose within the most commercial and improbable places.